Temperaturas e períodos de molhamento foliar no desenvolvimento da ferrugem alaranjada da cana-de-açúcar (Puccinia kuehnii) - de Lima, Lonjoré Leocádio [UNESP]; Scaloppi, Érika Auxiliadora Giacheto; Barreto, Lívia Felício [UNESP]; Barreto, Modesto [UNESP] (FapUNIFESP (SciELO), 2017)
Considering the lack of epidemiological studies on orange rust of sugarcane in Brazil and the importance of this crop in the Brazilian agribusiness, the aims of this study were to determine the influence of temperature and leaf wetness duration on the epidemiology of this disease. Twenty-day-old plants of the cultivar SP 89-1115 were inoculated with the fungus Puccinia kuehnii at a concentration of 2 x 104 urediniospores.mL. Experimental design was completely randomized (DIC), in 5x7 factorial arrangement, representing five temperatures (17.5, 20.0, 22.5, 25.0 and 27.5°C) and seven leaf wetness periods (0, 4, 8, 12, 16, 20 and 24 hours), including three replicates. Ideal temperatures for orange rust development were 20.0, 22.5 and 25.0°C, of which the latter was the best. At temperatures of 22.5 and 25.0°C, pustules increased in number with 20 hours leaf wetness but decreased with 24 hours wetness. No disease symptoms were observed at 0, 4 and 8 hours leaf wetness for all tested temperatures. Similarly, the disease did not occur at a temperature of 27.5°C for all tested combinations of leaf wetness duration. Epidemiological studies of this disease are important to devise control strategies and eventually develop a forecasting system for orange rust of sugarcane.
Temperatures and leaf wetness duration on orange rust development in sugarcane (Puccinia kuehnii)
Keywords: Epidemiology; Saccharum spp; Weather factors